-(x-8)+4=2(-10)+x

Simple and best practice solution for -(x-8)+4=2(-10)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x-8)+4=2(-10)+x equation:


Simplifying
-1(x + -8) + 4 = 2(-10) + x

Reorder the terms:
-1(-8 + x) + 4 = 2(-10) + x
(-8 * -1 + x * -1) + 4 = 2(-10) + x
(8 + -1x) + 4 = 2(-10) + x

Reorder the terms:
8 + 4 + -1x = 2(-10) + x

Combine like terms: 8 + 4 = 12
12 + -1x = 2(-10) + x

Multiply 2 * -10
12 + -1x = -20 + x

Solving
12 + -1x = -20 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
12 + -1x + -1x = -20 + x + -1x

Combine like terms: -1x + -1x = -2x
12 + -2x = -20 + x + -1x

Combine like terms: x + -1x = 0
12 + -2x = -20 + 0
12 + -2x = -20

Add '-12' to each side of the equation.
12 + -12 + -2x = -20 + -12

Combine like terms: 12 + -12 = 0
0 + -2x = -20 + -12
-2x = -20 + -12

Combine like terms: -20 + -12 = -32
-2x = -32

Divide each side by '-2'.
x = 16

Simplifying
x = 16

See similar equations:

| H(t)=20t-4.9t^2+2 | | a+32+45=15a-44 | | 9x-45=4x+24 | | 11/1/2 | | (2w+5)(w-7)=0 | | 28u-8+u+32=40u-9 | | -9x+5x=8 | | 3x+6(9x-7)=414 | | 4r+11=15 | | 2*-13-3-15=9 | | 2x-39=17 | | 4p+15+33=6p | | -(-8)+4=2(x)+-8 | | 15w-49+33=13w | | -8/3x=16/3 | | 49x+43=48x+45 | | z-32.56=12 | | -12x-14=-86 | | 2z+47=6z-16 | | 2(12y-11)=-4(1-6y) | | -(x-8)+4=2(12)+x | | 25=10+5j | | 5m^2+26m+5=0 | | 2x-3*-13=9 | | -(x-8)+4=2(-12)+x | | 7x+3(5-3x)=5 | | b+3+b=b+50 | | ly-8l+6=15 | | 3a+1=a+19 | | 15.08+w=30.08 | | Cosx/cos^2(2x) | | -5x-3*-13=30 |

Equations solver categories